Effect of Soybean-based Food Supplement on Insulin and Glucose Levels in Type 2 Diabetes Mellitus Patients - Purwoko, Akhmad Edy; Astuti, Indwiani; Asdie, Ahmad Husain; Sugiyanto, Sugiyanto (Indonesian Journal of Pharmacy, 2019)
Introduction: Indonesia is one of ten countries with the largest diabetic populations in the world. Giving soy supplements to people with diabetes can reduce blood glucose levels significantly. However, no studies have shown a reduction back to normal glucose levels. This study aimed to determine the increase of insulin levels and blood glucose suppression in glucose tolerance tests after supplementation of soy in patients with type 2 diabetes. Sequencing the gene of GLP-1 (37 amino acid). This experimental research was a randomized, treatment controlled; open clinical trial study conducted by comparing the control group treated with soybean supplement products containing 18g protein and placebo. Seventy-six treatment subjects with type 2 diabetes were recruited from Muhammadiyah Gamping Hospital and PERSADIA gymnastics group according to the inclusion and exclusion criteria and then grouped randomly in the supplement treatment and placebo groups. Blood sampling was drawn at 8 hours fasting, 2 hours after supplement administration and 2 hours after administration of 75g glucose for measuring blood insulin and glucose level. Blood insulin level 2 hours after supplement administration (mean±SEM) increased 5.3±0.8µIU/ml (n=37) while placebo decreased 0.9±0.4µIU/ml (n=39) which was statistically significantly different (p<0.05). Blood glucose levels increased in the glucose tolerance tests, while the supplement group was 130.0±11.5mg/dl (n=37) lower than the placebo 146.7±8.2mg/dl (n=39) (p>0.05). Gene sequencing shows a nucleotide variation of GLP-1 (37 amino acid) in Javanese T2DM Giving Soybean supplements containing 18g protein increased blood insulin levels and suppressed blood glucose levels in glucose tolerance tests.